Nous documents per a l'estudi de l'obra del pintor Joan Gascó - Galobart i Soler, Josep (Miscel·lània litúrgica catalana, 2016)
Presentation of three unpublished documents related to works by the painter Joan Gascó, chief of the most representative painting workshop in the region of Vic during the first half of 16th century.